The Long-run and Short-run Effects of Crude Oil Price on Methanol Market in Iran - Komijani, Akbar; Alikhani, Nadiya Gandali; Naderi, Esmaeil (International Journal of Energy Economics and Policy, 2012)
Substituting crude oil exports with value-added petrochemical products is one of the main strategies for policy makers in oil-driven economies to isolating the real sectors of economy from oil price volatility. This policy inclination has led to a body of literature in energy economics in recent decades. As a case study, this paper investigates the short-run and long-run relationship between Iran’s oil price and methanol price which is one of the most important non-oil exports of the oil-exporting country. To do so, the weekly data from 18 Jan. 2009 to 18 Sep. 2011 in a VECM framework is applied. The results show that in the long-run, oil price hikes leads to proportional increase in methanol price while in the short-run, this impact is not significant. Keywords: Crude Oil; Methanol; VECM Model JEL Classifications: Q43; C1; C32